Gridlock depicting dysfunction in transport infrastructure through grids and metonymy - Ragasa, John David R.; Abaya, Leo Antonio C. (Quezon City College of Fine Arts, University of the Philippines Diliman, 2019)
This thesis was inspired by the deficiencies of Transport Infrastructure in the Philippines, particularly in Metro Manila. This thesis is concerned with tackling the narratives of subpar quality of roads, the abysmal waiting times for public transportation, and the painfully slow and delayed construction projects that promise efficiency. Such structures and experiences have become ubiquitous and commonplace to the FIlipino commuter and to the artist.

The thesis artwork presented grids found in road and railway networks, and scaffolding from construction sites as the subject of the painting. The artist took cues from reactions to the modernist views of the grid according to the Constructivists and contemporary artists. Through this approach, the autonomy of the grid was replaced by its capacity to depict social narratives. Through physical manipulation, the destabilization of the grid reflected the dysfunction in the transport infrastructure. A metonymic approach in the use of materials was also used in the painting, which suggested an indexical mode of representation. This was achieved through the use of actual industrial materials, such as concrete, asphalt, and other materials used in construction, for painting.

The resulting artwork was an object painting that used urban imagery, such as the grid, that reflected the dysfunction of transport infrastructure in Metro Manila.
Thesis (Bachelor of Fine Arts in Painting)--University of the Philippines Diliman
Bibliography: leaves 32-34
Keywords: Transportation -- Metro Manila -- Philippines; Roads -- Metro Manila; Railroads -- Metro Manila; Painting; Grids (cartography) in art